Charge neutral halogen bonding tetradentate-iodotriazole macrocycles capable of anion recognition and sensing in highly competitive aqueous media - Thanthapatra Bunchuay (2022)
A series of neutral tetradentate halogen bonding (XB) macrocycles, comprising of two bis-iodotriazole XB donors were synthesised in 60-70% yields via a stepwise CuAAC-mediated cyclisation strategy. Extensive 1H NMR anion titration experiments reveal halide binding affinities are critically dependent on the substitution pattern of the xylyl spacer unit. The meta-substituted macrocycle remarkably displays cooperative tetradentate XB-halide anion recognition in highly competitive 40% aqueous-organic D2O/acetone-d6 (40 : 60, v/v) solvent mixtures. Integration of para-xylyl and naphthyl spacer units generates extended macrocyclic cavities, capable of selective oxalate recognition. Furthermore, preliminary fluorescence exeperiments reveal dicarboxylate specific sensing can be achieved through monitoring of the naphthylene centred emission. This journal is